Gambaran Strategi Koping Mahasiswa Keperawatan Yang Kembali Kuliah Tatap Muka Pada Masa Pandemi Covid-19 - Wenny, Bunga Permata; Purnamasari, Ita; Yeni, Fitra; Sarfika, Rika (REAL in Nursing Journal, 2023)
Background: During the current COVID-19 pandemic, causing an epidemiological and psychological crisis that creates concerns about the mental health of young people around the world which is a source of stress for students to carry out face-to-face learning directly, coping strategies are one of the efforts that can reduce stressors for students. The purpose of this study was to describe the coping strategies of nursing students who returned to face-to-face lectures during the COVID-19 pandemic. Methods: This research is a quantitative research that uses a descriptive design with a sample of 166 respondents, using a total sampling technique. The instrument used in this study is the Brief-Coping Behavior Questionnaire (Brief-COPE) for coping strategies. Results: The results of this study indicate that more students use problem focused coping strategies with an average of 5.77. Conclusion: This study suggests to students to use coping strategies in order to overcome stressors in students when conducting face-to-face learning directly or clinical practice in hospitals so that students can adapt so as not to interfere with student concentration and during the COVID-19 pandemic. Keywords: COVID-19; coping strategies; student